2022
DOI: 10.47593/2675-312x/20223502eabc293
|View full text |Cite
|
Sign up to set email alerts
|

Role of Strain in the Early Diagnosis of Diabetic Cardiomyopathy

Abstract: Background: Advanced echocardiography using two- and three-dimensional myocardial strain proposes to identify subclinical systolic dysfunction in different clinical conditions. Strain assessment plays an important role in the early diagnosis of diabetic cardiomyopathy in diabetes mellitus (DM). However, the findings of published articles are heterogeneous. Here we conducted a systematic review to analyze the current role of strain assessment in patients with DM. Methods: This systematic review of five database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
3
0
4
Order By: Relevance
“…Thais et al. summarized totally 27 studies, discovering that using 2D and 3D speckle-tracking echocardiography for measuring myocardial strain effectively detected subclinical systolic dysfunction among patients diagnosed with diabetes ( 33 ). However, their study was limited to studies on cardiomyopathy caused by diabetes, and only compared the differences in strain values between the cardiomyopathy group and the non-myocardial group.…”
Section: Discussionmentioning
confidence: 99%
“…Thais et al. summarized totally 27 studies, discovering that using 2D and 3D speckle-tracking echocardiography for measuring myocardial strain effectively detected subclinical systolic dysfunction among patients diagnosed with diabetes ( 33 ). However, their study was limited to studies on cardiomyopathy caused by diabetes, and only compared the differences in strain values between the cardiomyopathy group and the non-myocardial group.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то, что выраженного снижения ГПД у пациентов с СД2 не было (-17,6%), данный показатель статистически значимо отличался от такового в контрольной группе, где ГПД была <-18% (-19,9%, p<0,008). Недавно опубликованный систематический обзор продемонстрировал, что визуализация деформации миокарда с помощью двухили трехмерной СТЭ позволяет распознавать систолическую СДЛЖ у пациентов с СД [13]. Более того, когортное исследование с 10-летним наблюдением показало, что СДЛЖ, выявленная с помощью оценки ГПД, является независимым предиктором неблагоприятного прогноза течения СН у половины бессимптомных больных СД2 [14].…”
Section: Discussionunclassified
“…The level of NT-proBNP was significantly higher in the T2D and prediabetes groups compared to the control group, while in all three groups it did not exceed normal values (p<0,001). A higher level of NT-proBNP was associated with hypertension -odds ratio (OR) 3,64 [1,[2][3][4][5][6][7][8][9][10][11][12][13],04] (p=0,005), a decrease in LV ejection fraction -OR 1,25 [1,06-1 ,47] (p=0,007), concentric hypertrophy -OR 4,84 [1,41] (p=0,011) and decreased GLS -OR 1,85 [1,62-2,06] (p=0,005), an increase in the ratio of early and late diastolic transmitral flow (E/A) -OR 0,01 [0,008-0,416] (p=0,024) and isovolumic relaxation time (IVRT) -OR 1,08 [1,03-1,14] (p=0,03). The sensitivity and specificity of NT-proBNP as a test for predicting GLS reduction <-18% were 86 and 27%, respectively.…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…preclinical echocardiography, which is more sensitive than conventional echocardiography ( 28 ). In another systematic review by Silva et al, when conducting data aggregation on 19 studies using 2D STE (1774 patients with diabetes) and 9 studies using 3D STE (488 patients with diabetes), concluded Cardiac deformity imaging by STE 2D and STE 3D is valuable for early identification of preclinical systolic dysfunction, this difference becoming more apparent when combined with risk factors and status ventricular remodeling ( 35 ).…”
Section: Discussionmentioning
confidence: 99%